2022
DOI: 10.28926/riset_konseptual.v6i3.557
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception on The Use of WhatsApp for Learning Writing During Covid-19 Pandemic: A Case Study

Abstract: Writing skill is a complex skill that cannot be learned independently. Although students learn from home, they need a comprehensive understanding of theories and practical guidance from the teacher. Therefore, teachers use many media and applications that can support this online learning with various considerations. This research is conducted to find out the nine-grade students’ SMPN 04 Pare perception of the use of WhatsApp groups for learning writing. This research used a case study to identify students’ per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, the outcome demonstrates that one of the suitable learning environments for Indonesian education is the WhatsApp group. However, this study's results contradict Rosalinda et al [49], whose findings indicate that students' reactions to using WhatsApp to learn writing were positive. The study's findings further reveal that the learning activities conducted through WhatsApp and the use of the messaging app as a writing platform have piqued students' interest.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, the outcome demonstrates that one of the suitable learning environments for Indonesian education is the WhatsApp group. However, this study's results contradict Rosalinda et al [49], whose findings indicate that students' reactions to using WhatsApp to learn writing were positive. The study's findings further reveal that the learning activities conducted through WhatsApp and the use of the messaging app as a writing platform have piqued students' interest.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Rokhmah [48] used telecollaboration on Facebook and WhatsApp to investigate pupils' writing abilities, demonstrating that WhatsApp is a suitable learning tool for students, particularly to improve their language learning. Furthermore, Rosalinda et al [49] investigated how students perceive writing lessons while using WhatsApp, finding that students are enthusiastic and engaged in utilizing WhatsApp to learn writing. Nedal [50] discovered a substantial difference between the pretest and posttest writing scores of the journaling participants in his study, with statistically significant improvements observed in language choice and voice, two essential writing qualities.…”
Section: Introductionmentioning
confidence: 99%
“…Recount text is a good material to improve students' writing skill because students can make their own recount text, the result also shows positive feedback from the students. Moreover, Rosalinda et al, (2022) delve about students' perception when using WhatsApp during learning about writing. The result explain that students excited and interest to learn writing using WhatsApp.…”
Section: The Use Of Whatsapp In Writing Skillmentioning
confidence: 99%
“…Students gave the positive feedback about using WhatsApp that can be seen from their achievement. Moreover, Rosalinda et al, (2022) investigate about students' perception while using WhatsApp to learn about writing. Students like to use WhatsApp and they gave positive response about the use of WhatsApp during learning process.…”
Section: Introductionmentioning
confidence: 99%